Mouths and noses - Markham, Sally (Nelson Australia South Melbourne, Vic., 1994)
Mouths and Noses by Sally Markham is likely a children's book that introduces young readers to the functions and features of mouths and noses in a fun and engaging way. The book would explain how these parts of the body help with essential tasks like breathing, smelling, eating, and speaking. Through simple language and illustrations, it might explore the differences in mouths and noses across various animals and humans, encouraging curiosity about the body and its functions. This kind of book aims to combine education with enjoyment for early readers.